Saururus chinensis-controlled allergic pulmonary disease through NF-κB/COX-2 and PGE(2) pathways - Song, MiKyung (PeerJ, 2020)
Saururus chinensis is a perennial herb found in the northeastern regions of Asia, including Korea, China, and Japan, and is used in traditional medicine. Studies have identified the four major constituents in Saururus chinensis water extract (LHF618(®)) as miquelianin (11.75 ± 0.092 mg/g), rutin (1.20 ± 0.008 mg/g), quercitrin (2.38 ± 0.389 mg/g), and quercetin (0.068 ± 0.017 mg/g). Saururus chinensis can improve the symptoms of ovalbumin- or fine dust-induced allergic pulmonary disease by suppressing the effects of WBCs and neutrophils in BALF and IgE in the serum. Saururus chinensis dose-dependently recovered morphological changes such as mucous hyper secretion (from 2.7 ± 0.46 to 0.6 ± 0.65), pulmonary epithelial cell hyperplasia (from 2.4 ± 0.55 to 0.7 ± 0.67), and inflammatory cell infiltration (from 2.3 ± 0.45 to 0.6 ± 0.43), and effectively controlled cDNA levels and protein levels of IL-13. It inhibited NF-κB translocation and COX-2 protein synthesis and suppressed the expression of PGE(2). Our results show that Saururus chinensis controlled allergic pulmonary disease via the anti-inflammatory pathways, NF-κB/COX-2 and PGE(2). Saururus chinensis may be a promising drug candidate against fine dust-induced allergic pulmonary disease.